Synergy Between Academics and the Community in Increasing the Added Value of Local Food Products through Packaging Innovation: Duwet Polinema Catfish Nuggets - Widiyowati, Eny; Lestari, Baroroh; Nurdjizah, Nurdjizah; Poernamawati, Diana Eka; Zaini, Achmad; Anjari, Becik Gati (Transpublika Publisher, 2025)
Food product packaging plays a crucial role in determining market competitiveness, particularly for local food products in rural areas. Proper packaging not only preserves product quality but also significantly influences consumer purchasing decisions and product marketability. Despite the growing recognition of packaging importance, many small-scale food producers in Indonesia still face challenges in implementing standard packaging practices due to limited knowledge, resources, and access to modern packaging technology. This Community Service Program (PKM) was carried out by a team of lecturers from the Business Administration Department of the Malang State Polytechnic as an effort to increase the added value and competitiveness of the local food product “Duwet Polinema Catfish Nuggets” in Duwet Village, Tumpang District, Malang Regency. The main problems faced by the producer community are limited knowledge of product packaging and labeling, a lack of effective promotional strategies, and the unavailability of modern packaging equipment. The activities were carried out using a participatory approach through stages of socialization, technical training, promotional assistance, and the provision of vacuum sealer machine grants. The results of the activity showed an increase in the community's skills in packaging according to Good Manufacturing Practices (GMP) principles, an improvement in product quality through hygienic and aesthetic packaging, and a strengthening of digital promotion capabilities. The synergy between academics and the community proved to be effective in increasing the added value and competitiveness of local products based on fishery potential, while strengthening the community's economic independence in a sustainable manner.